Tactile Stimulation and Active-Assisted Exercise on Motor Function and Functional Ability of Upper Extremity in Post-Stroke Patients - Fahma Yulinda Ekasari; Prima Dewi Kusumawati; Agustin Widyowati; Siti Farida Noor Layla; Novita Ana Anggraini (Jurnal Kesehatan, 2025)
Post-stroke sensorimotor disorders are the leading cause of long-term disability in adults. The purpose of this research was to analyze the combined effect of tactile stimulation and active-assisted exercise on upper-extremity motor function and functional activity in post-stroke patients at Physio Dahsyat Home Care. A Quasi-Experimental Design was used with purposive sampling. Thirty participants were divided into two groups: Group A, a combination of tactile stimulation and active assisted exercise; and Group B, electrical stimulation and PNF. The average scores of FMA-UE and CAHAI-8 in Group A were 16.33 to 60.13 and 14.80 to 52.73. In Group B, the average score was 13.40 to 48.07 and 13.40 to 44.87. Paired t-tests showed p-values<0.001 for both Group A and Group B, indicating a significant effect in both groups. An independent test showed a significant. <0.001, indicating a comparison of the impact on motor function and functional activity of the upper extremity. The highest average scores for motor function and functional activity in Group A were 60.13 and 52.73. A combination of tactile stimulation and active-assisted exercise was more effective, leading to increased muscle strength through motor unit activation; the more motor units involved, the greater the increase in muscle strength.